Optimal modelling of non-revenue water: A case study of Lebohang extension 9 and 10 in Govan Mbeki Municipality, Mpumalanga, South Africa - Mlangeni, Ready Victor (Vaal University of Technology, 2023)
South Africa was declared a water scarce country with an annual runoff that is estimated to be less than 13 percent against the world average. South African municipalities are in position of providing accurate water balance data which is necessarily to measure the level of NRW. However, majority of them don’t keep accurate records of their input volume or billed consumption. The study done by South African Water Research Commission which analysed 62 system has estimated total water losses (real and apparent) to be 31 percent of total supplied water. (McKenzie: 2014) The global volume of non-revenue water (NRW) or water losses is overwhelming. Each year more than 32 billion m3 of treated water is lost through leakages from the distribution networks. An additional 16 billion m3 per year is delivered to consumers but not invoiced due to various reasons such as of theft, poor metering, inadequate billing systems, or illegal use. In some low-income countries this loss represents 50 -60 percent of water produced, with a global average estimated at 35 percent. Saving just this amount would supply water to an additional 100 million people without further investment in water production and distribution systems. (Simbeye I: 2010) Many studies conducted proved that water loss in South Africa is generally considered high between 30 percent and 70 percent and the cause of these high losses is defined in various studies (McKenzie & Seago: 2007). Many reasons have been tabled as contributing factors to the cause of high level of non-revenue water in general. The reasons include amongst others and not limited to poor planning, pressure management control, insufficient funds, and poor water network implementation. The factors further include inadequate actions in place to address optimization of services, leakage control, inadequate tariff, and collection systems. (Muhamad Shahbani Abu Bakar: 2005) The major challenges towards efficient and effective water delivery to all urban people are usually poor governance, financial constraints, poor network design, poor customer services, and inadequate infrastructure. It is obvious that high levels of NRW result from volumes of water lost through physical leaks or administrative losses from poor customer accounting and billing. This seriously affects the financial sustainability of water service providers. (Simbeye I: 2010)
M. Tech. (Department of Civil Engineering, Faculty of Engineering and Technology), Vaal University of Technology.
Keywords: Optimal modelling; Non-revenue water; Govan Mbeki Municipality; South African Water Commission; Dissertations, Academic -- South Africa.; Water leakage -- South Africa.